Applying flower writing strategy to the tenth graders in writing descriptive text - Yuliana; Rachmanita (Language and Education Journal, 2021)
Writing is regarded as a challenging subject in school. At the same time, it was a critical skill for students to master because it is so important in this age of globalization. This study aimed to find out whether or not the Flower Writing Strategy was effective to be used in teaching writing descriptive text. The quasi-experimental method was used in this study. The sample of the study was 68 students taken by using the purposive sampling technique. The data was gained by using a written test. The data were analyzed by using a t-test. Based on the result of the independent sample t-test, it was found that t-obtained (3.439) was higher than ttable (1.9955) and pvalue (0.001) was less than άvalue (0.05). It meant that the null hypothesis (Ho) was rejected and alternative hypothesis (Ha) were accepted. Hence, Flower Writing Strategy was effective to be used in teaching descriptive text.